A revision of the chigger genus Afrotrombicula (Acariformes: Trombiculidae) - Stekolnikov, Alexandr A. (Zootaxa, 2023)
The chigger genus Afrotrombicula Kolebinova and Vercammen-Grandjean, 1978 has been revised based on examination of museum specimens and reference data. Six species have been transferred to this genus from Neotrombicula Hirst, 1925 with the following new combinations: Afrotrombicula (Afrotrombicula) centrafricana (Goff, 1995), comb. nov., A. (A.) claviglia (Radford, 1948), comb. nov., A. (A.) kenyaensis (Goff, 1995), comb. nov., A. (A.) nicolei (Taufflieb, 1958), comb. nov., A. (A.) rickenbachi (Taufflieb, 1965), comb. nov., and A. (A.) zairiensis (Taufflieb, 1966), comb. nov. Re-descriptions of two incompletely described species have been provided. Four new synonyms have been established for two species: A. (A.) rickenbachi (Taufflieb, 1965), comb. nov. (= Neotrombicula cercopitheci cercopitheci Vercammen-Grandjean, 1965 (nomen nudum), syn. nov.; = N. chicapa Vercammen-Grandjean, 1965 (nomen nudum), syn. nov.; = N. kinduensis Vercammen-Grandjean, 1965 (nomen nudum), syn. nov.), and A. (Tauffliebicula) machadoi (Taufflieb, 1962) (= A. lophuromyia Kolebinova and Vercammen-Grandjean, 1978, syn. nov.). Afrotrombicula rickenbachi has been for the first time recorded in the Democratic Republic of the Congo and found on six new host species. A key to the 14 species referred to the genus Afrotrombicula has been compiled. According to the results of revision, the genus Afrotrombicula is an endemic of the Tropical Africa, and its distribution is probably restricted to subequatorial territories.